Molecular Dynamics Simulation and Density Functional Theory Study of Chemisorption of Propranolol Optical Isomers on a Uracil‐modified Carbon Paste Electrode. Issue 9 (26th July 2017) - Khamitov, Edward M.; Shayakhmetova, Regina Kh.; Sidelnikov, Artem V.; Maistrenko, Valery N.
Abstract : To reveal the nature of the interaction of the optical isomers of propranolol with the surface of carbon paste electrodes modified by uracil, we performed a combined computational and experimental study. Our study comprised the different modes of complexation between propranolol and uracil molecules covering the carbon paste electrode within two approaches: molecular dynamics simulation (MD) and quantum mechanics (QM) modeling. A graphene layer was used as a model of the carbon paste electrode. The computations showed that uracil modification of the carbon paste electrode surface enhanced the selectivity toward the D‐isomer of propranolol as compared to the unmodified case. These theoretical results agree with our voltammetric measurements. Abstract : Complex formation of propranolol enantiomers on carbon paste electrodes modified by uracil was studied. MD simulations show that modification of electrode surface enhances the selectivity. Weak interactions of propranolol were analyzed by reduced density gradient calculations. Voltammetric measurements were carried out with a three‐electrode system.